The immunogenicity and safety of a tetravalent measles-mumps-rubella-varicella vaccine when co-administered with conjugated meningococcal C vaccine to healthy children: A phase IIIb, randomized, multi-center study in Italy. Issue 36 (5th August 2016) - Durando, Paolo; Esposito, Susanna; Bona, Gianni; Cuccia, Mario; Desole, Maria Giuseppina; Ferrera, Giuseppe; Gabutti, Giovanni; Pellegrino, Angelo; Salvini, Filippo; Henry, Ouzama; Povey, Michael; Marchetti, Federico
Highlights: Open, randomized, phase IIIb study conducted at 13 centers in Italy. MMRV + MenC vaccine seroconversion rates non-inferior to separate MMRV/MenC vaccines. MenC vaccine did not alter the safety profile of MMRV vaccine administered alone. Co-administered MMRV and MenC vaccines could reduce number of clinic visits. Abstract: Introduction: Multiple vaccination visits and administrations can be stressful for infants, parents and healthcare providers. Multivalent combination vaccines can deliver the required number of antigens in fewer injections and clinic visits, while vaccine co-administration can also reduce the number of visits. This non-inferiority study was undertaken to evaluate the feasibility of co-administering a combined measles-mumps-rubella-varicella (MMRV) vaccine with conjugated meningococcal C (MenC) vaccine in a large cohort of healthy Italian toddlers. Methods: Healthy subjects aged 13–15 months were randomized (2:1:1) to receive single doses of either: co-administered MMRV + MenC at the same visit (MMRV + MenC group); or MMRV followed 42 days later by MenC (MMRV group); or MenC followed 42 days later by MMRV (MenC group). Blood samples were collected before and 43 days after vaccination. Antibody titers against MMRV were measured using ELISA. Functional-anti-meningococcal-serogroup activity (rSBAMenC) was assessed using a serum bactericidal test. Solicited local and general reactions were recorded for up to 4 and 42 days post-vaccination, respectively. Non-inferiority of MMRV + MenC to MMRV (post-dose-1 seroconversion rates) and MMRV + MenC to MenC (post-dose-1 seroprotection rates) was achieved if the lower limit (LL) of the 95% confidence interval (CI) for the group difference was ⩾−10% for each antigen. Results: 716 subjects were enrolled in the study. At 42 days post-vaccination, the MMRV seroconversion rates were 99.3% (measles), 94.5% (mumps), 100% (rubella) and 99.7% (varicella) in the MMRV + MenC group, and 99.4%, 93.2%, 100% and 100%, respectively, in the MMRV group. The seroprotection rates against rSBA-MenC were 98.3% in the MMRV + MenC group and 99.3% in the MenC group. Non-inferiority was reached for all the vaccine antigens. The safety profiles were as expected for these vaccines. Conclusion: The immune responses elicited by co-administered MMRV + MenC were non-inferior to those elicited by MMRV or MenC alone and support vaccination of children with both vaccines at a single visit. Clinical Trials registration:NCT01506193 .